Latitudinal variation in the abundance of methane (CH4) above the clouds in Neptune's atmosphere from VLT/MUSE Narrow Field Mode Observations - Irwin, P; Toledo Carrasco, D; Braude, A; Bacon, R; Weilbacher, P; Teanby, N; Fletcher, L; Orton, G (Elsevier, 2019)
Observations of Neptune, made in 2018 using the new Narrow Field Adaptive Optics mode of the Multi Unit Spectroscopic Explorer (MUSE) instrument at the Very Large Telescope (VLT) from 0.48 to 0.93 μm, are analysed here to determine the latitudinal and vertical distribution of cloud opacity and methane abundance in Neptune's observable troposphere (0.1–∼ 3bar). Previous observations at these wavelengths in 2003 by HST/STIS (Karkoschka and Tomasko 2011, Icarus 205, 674–694) found that the mole fraction of methane above the cloud tops (at ∼ 2 bar) varied from ∼ 4% at equatorial latitudes to ∼ 2% at southern polar latitudes, by comparing the observed reflectivity at wavelengths near 825 nm controlled primarily by either methane absorption or H2–H2/H2–He collision-induced absorption. We find a similar variation in cloud-top methane abundance in 2018, which suggests that this depletion of methane towards Neptune's pole is potentially a long-lived feature, indicative of long-term upwelling at mid-equatorial latitudes and subsidence near the poles. By analysing these MUSE observations along the central meridian with a retrieval model, we demonstrate that a broad boundary between the nominal and depleted methane abundances occurs at between 20 and 40°S. We also find a small depletion of methane near the equator, perhaps indicating subsidence there, and a local enhancement near 60–70°S, which we suggest may be associated with South Polar Features (SPFs) seen in Neptune's atmosphere at these latitudes. Finally, by the use of both a reflectivity analysis and a principal component analysis, we demonstrate that this depletion of methane towards the pole is apparent at all locations on Neptune's disc, and not just along its central meridian.